2006
DOI: 10.1021/jp0560011
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Aromaticity of Transition States in Pericyclic Reactions

Abstract: The aromaticity of transition states in pericyclic reactions such as electrocyclic reactions, cycloaddition reactions, and sigmatropic shifts was studied by the IDA (index of deviation from aromaticity) on the basis of a CASSCF wave function. The aromaticity defined by the IDA classified the allowed and forbidden transition states of pericyclic reactions treated here. The order of the aromaticity levels corresponds to that of the energy barriers of some reactions. The difference between the aromaticity defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 70 publications
2
42
0
Order By: Relevance
“…In the disubstituted series, rearrangement barriers have been shown to be lowered by π -donor groups, and the position of equilibrium was found to correlate with the BCO stabilization effects of the substituents. 5 A DFT investigation of the Cope rearrangement of the cyclobiphenalenyl (1) has shown it to occur via the unusual diradical (2), stabilized by π -dimerization, and having an unusually long inter-phenalenyl distance (comparable to the inter-allyl distance in a classical Cope rearrangement) of ∼2.8Å. 6 (1) (2) Calculations of the interactions between matured catalytic antibody AZ28 and the different conformers and enantiomers of 2,5-diaryl-hexa-1,5-dien-3-ol, allowing for the flexibility of the antibody, have reproduced, qualitatively only, the observed selectivity of the antibody for the S,equatorial substrate.…”
Section: All-carbon Pericyclic Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the disubstituted series, rearrangement barriers have been shown to be lowered by π -donor groups, and the position of equilibrium was found to correlate with the BCO stabilization effects of the substituents. 5 A DFT investigation of the Cope rearrangement of the cyclobiphenalenyl (1) has shown it to occur via the unusual diradical (2), stabilized by π -dimerization, and having an unusually long inter-phenalenyl distance (comparable to the inter-allyl distance in a classical Cope rearrangement) of ∼2.8Å. 6 (1) (2) Calculations of the interactions between matured catalytic antibody AZ28 and the different conformers and enantiomers of 2,5-diaryl-hexa-1,5-dien-3-ol, allowing for the flexibility of the antibody, have reproduced, qualitatively only, the observed selectivity of the antibody for the S,equatorial substrate.…”
Section: All-carbon Pericyclic Systemsmentioning
confidence: 99%
“…5 A DFT investigation of the Cope rearrangement of the cyclobiphenalenyl (1) has shown it to occur via the unusual diradical (2), stabilized by π -dimerization, and having an unusually long inter-phenalenyl distance (comparable to the inter-allyl distance in a classical Cope rearrangement) of ∼2.8Å. 6 (1) (2) Calculations of the interactions between matured catalytic antibody AZ28 and the different conformers and enantiomers of 2,5-diaryl-hexa-1,5-dien-3-ol, allowing for the flexibility of the antibody, have reproduced, qualitatively only, the observed selectivity of the antibody for the S,equatorial substrate. 7 Doubly α,β-unsaturated N -arylimines (3) have been shown to react with α,β-unsaturated ketenes to give azocinones (4), …”
Section: All-carbon Pericyclic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…With this analysis we intend to get an insight into the relationship between reactivity and aromaticity in pericyclic reactions. In previous works, it has Scheme 1 Schematic representation of reactants and product of the cycloaddition reaction between two cyclobutadiene molecules Scheme 2 Schematic representation of reactants and product of the cycloaddition reaction between two benzene molecules been shown that usually thermally allowed cycloadditions take place through aromatic transition states (TSs) [33], while TSs of thermally forbidden reactions are less aromatic or antiaromatic [34][35][36]. As recommended by several authors [20,[37][38][39][40][41], in the present work the local aromaticity of the 4-and 6-MRs has been measured using a set of differently based aromaticity criteria, to take into account the multidimensional character of aromaticity [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%